CORPORATE GOVERNANCE AND ACCOUNTING IRREGULARITIES: Evidence from the Two-tiered Board Structure in Indonesia - Jaswadi JASWADI; Nicholas Billington; Stella Sofocleous (APMBA (Asia Pacific Management and Business Application), 2012)
This study aims to investigate the extent to which the Indonesian corporate governance mechanism acts as an effective tool for protecting financial statements users against accounting irregularities. Considering that accounting irregularities might occur in between error and the fraud act, this study reviews the literature on minimizing the seriousness of these reporting incidences. The level of seriousness in misstatements is more severe when: (1) there is absence of financial expert(s) on supervisory boards and audit committees, (2) companies have short tenured-CEOs and poor internal control systems, and (3) auditors are solely appointed by firms’ BOCs without agreement of block holders (known as referral). In addition, an examination of simultaneous effects of each corporate governance dimension reveals a general weakness of the BOCs and their audit committees. However, the BOC and audit committee could be an effective tool in mitigating reporting incidences, especially when they show high-quality collaboration.